ANALISIS RASIO NET PROFIT MARGIN, RETURN ON INVESTMENT DAN RETURN ON EQUITY DALAM MENILAI KINERJA KEUANGAN PT. INDOMARCO PRISMATAMA TAHUN 2014 - 2018 - Parso Parso; Ayu Permata Sunan (REMITTANCE: JURNAL AKUNTANSI KEUANGAN DAN PERBANKAN, 2022)
The purpose of this study is to analyze the ratio of net profit margin, return on investment and return on equity in assessing the financial performance of PT Indomarco Prismatama for five periods from 2014 to 2018. The methodology used is a qualitative descriptive method, to analyze a company's financial statements. This research was conducted by data analysis techniques used by comparing the financial statements of income and balance for five periods, namely 2014-2018. The results showed that the highest net profit margin ratio occurred in 2017 and 2018. While the lowest net profit margin ratio occurred in 2016 due to an increase in general and administrative costs, causing a decrease in profit. The highest return on investment ratio occurred in 2018. While the return on investment ratio The lowest investment occurred in 2014 due to less than the maximum in generating profits with all the assets it owns. The highest return on equity ratio occurred in 2014. While the lowest return on equity ratio occurred in 2016 due to less than the maximum in generating profits with available capital. So that it can be said that financial performance is assessed from the results of the analysis of the three ratios, which are not good and unstable and are also still below the average industry standard